Method development and validation of paracetamol drug by RP-HPLC - T.A. Phazna Devi (Journal of Medical and Allied Sciences, 2013)
A simple and reproducible method was developed for paracetamol by Reverse Phase High Performance Liquid Chromatography (RP-HPLC). Paracetamol was separated on C18 column [4.6x250mm, particle size 5μm], using ortho phosphoric acid buffer with pH of 3.5 at the UV detection of 207nm. Isocratic elution of acetonitrile (ACN) and water was used as a mobile phase with various ratios and flow rates, eventually 25:75 v/v ACN and water was being set with the flow rate of 1mL/min. The statistical validation parameters such as linearity, accuracy, precision, inter-day and intraday variation were checked, further the limit of detection and limit of quantification of paracetamol concentrations were found to be 120ng/mL and 360ng/mL. Recovery and assay studies of paracetamol were within 99 to 102% indicating that the pro-posed method can be adoptable for quality control analysis of paracetamol.